Driving Factors of Urban–Rural Human Settlement Changes and a Multi-Scenario Simulation Based on SDGs - Yang Ye; Yantong Liu; Jingyi Liu; Zhiyi Weng; Ziyao Chang; Xiong Li (Ecosystem Health and Sustainability)
With industrialization, urbanization, and rapid changes in urban–rural human settlements, threats to sustainable development have raised global concerns. Human settlements are composed of “production–living–ecological” spaces (PLESs), where changes result from the combined influence of natural and socioeconomic factors. Currently, the spatiotemporal patterns of PLES and their driving factors, along with their compatibility with sustainable development goals (SDGs), remain unclear. This study focuses on the Beijing–Tianjin–Hebei Urban Agglomeration and Beijing as case studies, constructing a quality evaluation system for human settlements to reveal the driving factors behind PLES changes. We established a linkage between PLES, ecosystem service value, and SDGs and conducted multi-scenario simulations to assess future possibilities. From 1980 to 2020, we observed a marked shrinkage in production space (2,035.46 km2) and an expansion of living space (1,926.78 km2). The primary driving factors of PLES expansion included highways, population growth, and elevation, contributing 16.5%, 29.6%, and 36.4% to production, living, and ecological spaces, respectively. The ecosystem service value and SDG values gradually increased, displaying a clustering pattern of northern highs and southern lows. Among the various SDGs, SDG8 (decent work and economic growth) had the lowest value, while SDG15 (life on land) had the highest value. The production priority zone was primarily located in the southern urban fringe, whereas the central area and northern region prioritized living and ecological needs, respectively. The highest SDG values (1.40 to 1.63 yuan/m2) will be reached under an optimal scenario, highlighting the urgent need for differentiated policies for sustainable development in various contexts.